BEHAVIOUR OF FINANCIAL MARKETS DURING THE SUBPRIME CRISIS (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2016)
The objective of this article is to highlight the nature of the relationship between several stock markets (France, the great Britain, Germany, and United States). The behavior of those facing the subprime crisis that took place in United State markets we tried to analyze in August 2007. Empirically to make think back to these questions, we relied primarily on testing correlation. The result of this test demonstrates the significant increase in the correlation between stock markets: US, French, Germany and Britain during the period of the crisis. We interpret this increase as evidence of contagion. Secondly, it was based on the theory of co-integration. The results of the co-integration tests show the existence of three co-integration relationships between the most stock markets. The existence of co-integration relationship is evidence of contagion and integration of stock markets. Thirdly, we tried to apply the causality test between stock indices. The result of this test shows the existence of several causality between these indices confirming the importance of contagion during the crisis.